Preparation method and application of selenium-doped CdS / MoS2 heterojunction

By using a selenium-doped CdS/MoS2 heterojunction preparation method to control the band structure and morphology, the problems of high recombination rate of photogenerated carriers and severe photocorrosion in existing composite materials were solved, and the high efficiency of photoelectrocatalytic performance and stability were improved.

CN121222446APending Publication Date: 2025-12-30LULIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511492239.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2025-12-30

AI Technical Summary

Technical Problem

Existing composite materials have high photogenerated carrier recombination rates, reduced photocatalytic activity, insufficient active sites, severe photocorrosion, poor structural stability, narrow spectral response range, and low utilization of long-wavelength visible light.

Method used

By using a selenium-doped CdS/MoS2 heterojunction preparation method, the selenium doping amount is controlled to form a spiral morphology, optimize the band structure, enhance the light absorption range, promote the separation of photogenerated electron-hole pairs, reduce the interfacial resistance, and improve the photocatalytic performance.

Benefits of technology

It significantly improves the photoelectrocatalytic performance of selenium-doped CdS/MoS2 heterojunctions, increases active sites, optimizes carrier migration pathways, enhances photocatalytic efficiency and stability, and expands the spectral response range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121222446A_ABST
    Figure CN121222446A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a selenium-doped CdS / MoS2 heterojunction, and the preparation method comprises the following steps: preparing selenium-doped cadmium sulfide nanoparticles by using selenium powder as a selenium source, cadmium chloride as a cadmium source and thiourea as a sulfur source through a hydrothermal method, and successfully preparing a selenium-doped CdS / MoS2 heterojunction composite material by using ammonium molybdate as a molybdenum source through a hydrothermal method. Selenium doping obviously widens the visible light absorption range of cadmium sulfide, and the cadmium sulfide can be used for photocatalytic degradation of organic pollutants, hydrogen production through photoelectrochemical water decomposition, solar cell interface layers or photoelectrochemical sensors.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to a preparation method and application of a nanocomposite material, in particular to a preparation method and application of a selenium-doped CdS / MoS2 heterojunction. BACKGROUND

[0002] The existing composite material has a high photogenerated carrier recombination rate, resulting in reduced photocatalytic activity. The catalytic active edge sites are few, and the active sites are insufficient, which limits the catalytic performance. The photo corrosion is serious, resulting in poor structural stability. The spectral response range is narrow, and the utilization rate of long-wavelength visible light (such as near-infrared light) is low. SUMMARY

[0003] The application aims to provide a preparation method and application of a selenium-doped CdS / MoS2 heterojunction, which can overcome the problems of high photogenerated carrier recombination rate, serious photo corrosion and insufficient active sites in the prior art.

[0004] To achieve the above-mentioned purpose, the application provides the following technical scheme.

[0005] A preparation method of a selenium-doped CdS / MoS2 heterojunction comprises the following steps:

[0006] S1: 0.20g of cadmium dichloride and 0.38g of thiourea are ultrasonically dispersed and dissolved in 50mL of deionized water to obtain a first mixed solution;

[0007] S2: selenium powder is added to the first mixed solution and stirred uniformly, and then the mixture is subjected to hydrothermal reaction at 180 DEG C for 12 hours to obtain a second mixed solution;

[0008] S3: the second mixed solution is subjected to centrifugal washing with deionized water and anhydrous ethanol alternately, and then dried to obtain selenium-doped CdS nanoparticles;

[0009] S4: 0.26g of molybdenum ammonium molybdate tetrahydrate, 0.38g of thiourea and 0.26g of selenium-doped CdS nanoparticles are ultrasonically dispersed and dissolved in 50mL of deionized water to obtain a third mixed solution;

[0010] S5: the third mixed solution is subjected to hydrothermal reaction at 200 DEG C for 12 hours to obtain a fourth mixed solution;

[0011] S6: the fourth mixed solution is subjected to centrifugal washing with deionized water and anhydrous ethanol alternately, and then dried to obtain a selenium-doped CdS / MoS2 heterojunction.

[0012] Further, in step S2, the doping amount of the selenium powder is 0.05-0.15g.

[0013] Further, in step S2 or S5, the hydrothermal reaction is carried out in a blast drying oven, and the mixed solution is taken out when it is naturally cooled to room temperature.

[0014] Further, in step S3 or S6, the deionized water and anhydrous ethanol are alternately used for centrifugal washing more than 3 times, respectively.

[0015] Further, in step S3, the selenium-doped CdS nanoparticles are obtained by drying at 60 DEG C for 6 hours in a blast drying oven.

[0016] Further, in step S6, the selenium-doped CdS / MoS2 heterojunction is obtained by drying at 70 DEG C for 2 hours in a blast drying oven.

[0017] Further, the prepared selenium-doped CdS / MoS2 heterojunction has a spiral pattern.

[0018] The application further provides an application of the selenium-doped CdS / MoS2 heterojunction, and the selenium-doped CdS / MoS2 heterojunction prepared by the preparation method is used for photocatalytic degradation of organic pollutants, photoelectrochemical water splitting for hydrogen production, solar cell interface layer or photoelectrochemical sensor.

[0019] Compared with the prior art, the application has the beneficial effects that: by regulating the selenium doping amount to optimize the energy band structure of CdS, and combining the layered characteristics of CdS / MoS2, the heterojunction with a spiral pattern is constructed, and the photoelectrocatalytic performance of the selenium-doped CdS / MoS2 heterojunction composite material is significantly improved. The method is simple in process and low in cost, and the obtained selenium-doped CdS / MoS2 heterojunction has a wide application prospect in the fields of photocatalysis, solar cells and sensors. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 The figure is a flow chart of the preparation method of the selenium-doped CdS / MoS2 heterojunction.

[0021] Figure 2 The figure is a comparison of the morphology of the prepared selenium-doped CdS / MoS2 heterojunction with the spiral pattern of the local specialty food "millet noodles" in northwest China.

[0022] Figure 3 The figure is a comparison of the polycrystalline X-ray diffraction of the prepared selenium-doped CdS / MoS2 heterojunction containing 0.05 g, 0.10 g and 0.15 g selenium and pure CdS and pure MoS2.

[0023] Figure 4The scanning electron microscope (SEM) images of 0.05g selenium-doped CdS / MoS2 heterojunction prepared by the present application, wherein the three images from left to right represent different magnifications, and the magnification is getting larger and larger.

[0024] Figure 5 The scanning electron microscope (SEM) images of 0.10g selenium-doped CdS / MoS2 heterojunction prepared by the present application, wherein the three images from left to right represent different magnifications, and the magnification is getting larger and larger.

[0025] Figure 6 The scanning electron microscope (SEM) images of 0.15g selenium-doped CdS / MoS2 heterojunction prepared by the present application, wherein the three images from left to right represent different magnifications, and the magnification is getting larger and larger.

[0026] Figure 7 The SEM images and corresponding EDS images of 0.05g, 0.10g and 0.15g selenium-doped CdS / MoS2 heterojunction prepared by the present application.

[0027] Figure 8 The X-ray photoelectron spectroscopy (XPS) images of selenium-doped CdS / MoS2 heterojunction prepared by the present application.

[0028] Figure 9 The solid ultraviolet-visible diffuse reflectance spectroscopy (UV-Vis DRS) images of 0.05g, 0.10g and 0.15g selenium-doped CdS / MoS2 heterojunction prepared by the present application.

[0029] Figure 10 The indirect band gap energy images of 0.05g, 0.10g and 0.15g selenium-doped CdS / MoS2 heterojunction and pure CdS prepared by the present application.

[0030] Figure 11 The photocatalytic degradation rate images of 0.05g, 0.10g and 0.15g selenium-doped CdS / MoS2 heterojunction prepared by the present application.

[0031] Figure 12 The degradation rate images of 0.10g selenium-doped CdS / MoS2 heterojunction added with a capture agent prepared by the present application. DETAILED DESCRIPTION

[0032] With reference to the accompanying drawings, the technical solutions in the embodiments of the present application will be described clearly and completely. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the scope of the present application.

[0033] As shown in the figure, the present application is a preparation method of a selenium-doped CdS / MoS2 heterojunction, comprising the following steps: Figure 1

[0034] S1: ultrasonic dispersion and dissolution of 0.20 g of cadmium dichloride and 0.38 g of thiourea in 50 mL of deionized water to obtain a first mixed solution;

[0035] S2: adding selenium powder to the first mixed solution and stirring uniformly, and then hydrothermal reaction at 180℃ for 12 hours to obtain a second mixed solution;

[0036] S3: centrifugal washing of the second mixed solution with deionized water and anhydrous ethanol alternately, and drying to obtain selenium-doped CdS nanoparticles;

[0037] S4: ultrasonic dispersion and dissolution of 0.26 g of molybdenum ammonium sulfate tetrahydrate, 0.38 g of thiourea and 0.26 g of selenium-doped CdS nanoparticles in 50 mL of deionized water to obtain a third mixed solution;

[0038] S5: hydrothermal reaction of the third mixed solution at 200℃ for 12 hours to obtain a fourth mixed solution;

[0039] S6: centrifugal washing of the fourth mixed solution with deionized water and anhydrous ethanol alternately, and drying to obtain a selenium-doped CdS / MoS2 heterojunction.

[0040] The present application utilizes selenium-doped CdS to regulate the electronic structure, that is, introducing selenium atoms into the CdS lattice by hydrothermal method to form a Se-CdS solid solution, reducing the band gap (adjustable to ~2.1 eV) and enhancing the visible light absorption range (such as extending to 650 nm). Selenium doping can also induce lattice distortion to form defect energy levels, promoting the separation of photo-generated electron-hole pairs. In the growth process of the selenium-doped CdS / MoS2 heterojunction, the phase structure of MoS2 (1T / 2H mixed phase) is regulated, the metallicity (1T phase) is improved to enhance the conductivity, and the in-situ sulfidation method is used to ensure the formation of a close interface contact between CdS and MoS2, thereby reducing the interface resistance. The prepared selenium-doped CdS / MoS2 heterojunction has a spiral texture, increasing the specific surface area and exposing active sites, and also endowing the composite material with an internal strain field, optimizing the carrier migration path and reducing the loss of recombination.

[0041] Example 1 ​

[0042] A method for preparing a selenium-doped CdS / MoS2 heterojunction includes the following steps:

[0043] Step 1: Preparation of selenium-doped CdS nanoparticles. Dissolve 0.20 g of cadmium dichloride (CdCl2) and 0.38 g of thiourea (CH4N2S) in 50 mL of deionized water and ultrasonically disperse until completely dissolved. Add 0.05 g of selenium powder to the mixed solution, stir well, transfer to a reaction vessel, and place in a forced-air drying oven for hydrothermal reaction at 180 °C for 12 hours. Remove after natural cooling to room temperature.

[0044] Step 2: Wash the mixed solution by centrifugation at least three times, alternating between deionized water and anhydrous ethanol. Dry the precipitate in a forced-air drying oven at 60°C to obtain selenium-doped CdS nanoparticles.

[0045] Step 3: Dissolve 0.26g ammonium molybdate tetrahydrate (chemical formula (NH4)2MoO4·4H2O), 0.38g thiourea, and 0.26g selenium-doped CdS nanoparticles in 50mL of deionized water and ultrasonically disperse until completely dissolved. Transfer the mixed solution to a reaction vessel and place it in a forced-air drying oven for hydrothermal reaction at 200℃ for 12 hours. Remove it after natural cooling to room temperature.

[0046] Step 4: Wash the mixture several times with deionized water and anhydrous ethanol, then dry at 70°C to obtain the selenium-doped CdS / MoS2 heterojunction. Wash the mixed solution alternately with deionized water and anhydrous ethanol by centrifugation at least three times. Place the precipitate in a forced-air drying oven and dry at 70°C for 2 hours to obtain the selenium-doped CdS / MoS2 heterojunction.

[0047] Example 2

[0048] A method for preparing a selenium-doped CdS / MoS2 heterojunction includes the following steps:

[0049] Step 1: Preparation of selenium-doped CdS nanoparticles. Dissolve 0.20 g of cadmium dichloride (CdCl2) and 0.38 g of thiourea (CH4N2S) in 50 mL of deionized water and ultrasonically disperse until completely dissolved. Add 0.10 g of selenium powder to the mixed solution, stir well, transfer to a reaction vessel, and place in a forced-air drying oven for hydrothermal reaction at 180 °C for 12 hours. Remove from the oven after natural cooling to room temperature.

[0050] Step 2: Wash the mixed solution by centrifugation at least three times, alternating between deionized water and anhydrous ethanol. Dry the precipitate in a forced-air drying oven at 60°C to obtain selenium-doped CdS nanoparticles.

[0051] Step 3: Dissolve 0.26g ammonium molybdate tetrahydrate (chemical formula (NH4)2MoO4·4H2O), 0.38g thiourea, and 0.26g selenium-doped CdS nanoparticles in 50mL of deionized water and ultrasonically disperse until completely dissolved. Transfer the mixed solution to a reaction vessel and place it in a forced-air drying oven for hydrothermal reaction at 200℃ for 12 hours. Remove it after natural cooling to room temperature.

[0052] Step 4: Wash the mixture several times with deionized water and anhydrous ethanol, then dry at 70°C to obtain the selenium-doped CdS / MoS2 heterojunction. Wash the mixed solution alternately with deionized water and anhydrous ethanol by centrifugation at least three times. Place the precipitate in a forced-air drying oven and dry at 70°C for 2 hours to obtain the selenium-doped CdS / MoS2 heterojunction.

[0053] Example 3

[0054] A method for preparing a selenium-doped CdS / MoS2 heterojunction includes the following steps:

[0055] Step 1: Preparation of selenium-doped CdS nanoparticles. Dissolve 0.20 g of cadmium dichloride (CdCl2) and 0.38 g of thiourea (CH4N2S) in 50 mL of deionized water and ultrasonically disperse until completely dissolved. Add 0.15 g of selenium powder to the mixed solution, stir well, transfer to a reaction vessel, and place in a forced-air drying oven for hydrothermal reaction at 180 °C for 12 hours. Remove from the oven after natural cooling to room temperature.

[0056] Step 2: Wash the mixed solution by centrifugation at least three times, alternating between deionized water and anhydrous ethanol. Dry the precipitate in a forced-air drying oven at 60°C to obtain selenium-doped CdS nanoparticles.

[0057] Step 3: Dissolve 0.26g ammonium molybdate tetrahydrate (chemical formula (NH4)2MoO4·4H2O), 0.38g thiourea, and 0.26g selenium-doped CdS nanoparticles in 50mL of deionized water and ultrasonically disperse until completely dissolved. Transfer the mixed solution to a reaction vessel and place it in a forced-air drying oven for hydrothermal reaction at 200℃ for 12 hours. Remove it after natural cooling to room temperature.

[0058] Step 4: Wash the mixture several times with deionized water and anhydrous ethanol, then dry at 70°C to obtain the selenium-doped CdS / MoS2 heterojunction. Wash the mixed solution alternately with deionized water and anhydrous ethanol by centrifugation at least three times. Place the precipitate in a forced-air drying oven and dry at 70°C for 2 hours to obtain the selenium-doped CdS / MoS2 heterojunction.

[0059] To make the cadmium dichloride and thiourea solutions in the above three embodiments exactly the same, generally, 0.60 g of cadmium dichloride and 1.14 g of thiourea are taken together and dissolved in 150 mL of deionized water, ultrasonicated until completely dissolved, and after complete dissolution, it is equally divided into 3 portions, and 0.05 g, 0.10 g, and 0.15 g of selenium powder are added to them respectively for carrying out.

[0060] The present invention adopts a controllable segmented two-step hydrothermal in-situ growth method, that is, by first synthesizing selenium-doped CdS nanoparticles, in which the lattice distortion and defect sites induced by selenium doping are directly introduced through one-step hydrothermal method without subsequent annealing treatment, reducing energy consumption and impurity risk; then hydrothermally in-situ growing to uniformly anchor MoS2 nanosheets on the surface of selenium-doped CdS, forming a tight chemical bonding interface, realizing precise regulation of the heterojunction interface structure, that is, regulating the crystal nucleation and growth process in stages, and realizing the precise construction of the heterojunction interface structure and uniform composite of components. And the whole process of the present invention uses water as a solvent, the reaction temperature is moderate (≤200 °C), and the process is more environmentally friendly and suitable for large-scale preparation.

[0061] The present invention constructs a novel selenium-doped CdS / MoS2 heterojunction composite material by introducing selenium doping and spiral structure regulation. Selenium doping can effectively adjust the energy band structure of CdS, enhance the light absorption range, form a gradient energy band arrangement with MoS2, promote the Z-type charge transfer path, significantly improve the separation efficiency of photo-generated carriers, and at the same time reduce the carrier recombination rate; while the spiral morphology (such as Figure 2 , in the shape of a spiral similar to the local special pasta "莜面鱼鱼" in northwest China) optimizes the interface contact by increasing the specific surface area and exposing more active sites, and enhances the catalytic activity by modifying the edge of MoS2, further improving the photocatalytic efficiency and stability of the heterojunction. In addition, the spiral structure endows the material with a unique stress field and defect engineering, synergistically optimizing the separation and transport dynamics of photo-generated charges.

[0062] The preparation methods of the above three embodiments are used to respectively prepare selenium-doped CdS / MoS2 heterojunctions with three different doping amounts.

[0063] For these three selenium-doped CdS / MoS2 heterojunctions with different doping amounts, the present invention uses a polycrystalline X-ray diffractometer (abbreviated as XRD pattern, and its parameters are set as follows: the target voltage is 36 kV, the target current is 20 mA, the step width is 0.04 °, the scanning speed is 4 ° / min, and a comprehensive scan is carried out for the 2θ angle range from 5 ° to 90 °) to characterize its structure as Figure 3 . The left diagram shows the absorption peaks of the selenium-doped CdS / MoS2 heterojunctions with three different doping amounts, and the right diagram shows the absorption peaks of pure CdS and pure MoS2.

[0064] As shown in the figure, with the increase of selenium doping, the CdS(002) absorption peak gradually shifts from 28.0° to a lower angle (specifically 28.0°→24.3°→23.5°), indicating that the main absorption peak of CdS has shifted, that is, selenium atoms (radius > sulfur atoms) have been successfully incorporated into the CdS lattice, resulting in lattice expansion. The absorption peak intensity of MoS2(002) decreases with the increase of selenium doping, while the full width at half maximum (FWHM) increases, indicating that the number of MoS2 layers decreases or the stacking order decreases, which may enhance the exposure of surface active sites.

[0065] For other impurity absorption peaks, no characteristic absorption peaks of CdSe or MoSe2 were observed in the highly selenium-doped sample, indicating that selenium exists as a dopant rather than an independent phase. Compared to pure CdS, the optical absorption edge of the selenium-doped CdS / MoS2 heterojunction is significantly shifted towards longer wavelengths (covering ultraviolet, visible, and near-infrared light), indicating that its light-trapping ability is enhanced.

[0066] For the three selenium-doped CdS / MoS2 heterojunctions with different doping levels mentioned above, the present invention also uses scanning electron microscopy (SEM) to characterize their structures, as follows: Figure 4 , Figure 5 and Figure 6 In each image, the target area is first located at low magnification during imaging, and then gradually focused to high magnification (e.g., 50,000×) to observe the microscopic morphology. The magnification of the three images from left to right increases sequentially.

[0067] from Figure 4 It is known that MoS2 tends to uniformly coat the CdS surface, forming a core-shell structure, significantly increasing the contact area at the heterojunction. And... Figure 5 This indicates that the CdS surface exhibits significant porosity, and its composite effect with MoS2 is even better. Specifically, as the selenium doping concentration increases, the CdS rod-like structure gradually shortens, the surface roughness increases, and porous or nanoparticle accumulation occurs. Figure 6 In the highly selenium-doped samples, the CdS particle size further decreased and exhibited irregular aggregation, possibly due to altered growth kinetics caused by lattice distortion. The number of MoS2 nanosheet layers decreased, and the edges showed increased curling or wrinkling, exposing more active edge sites.

[0068] Figure 7 To observe the SEM images (left image) and corresponding EDS images (right image) of three selenium-doped CdS / MoS2 heterojunctions with different doping amounts using scanning electron microscopy, so as to further analyze their morphology and elemental distribution.

[0069] The uniform distribution of cadmium, sulfur, and molybdenum in the heterojunction region, as shown in the figure, indicates that the selenium signal highly overlaps with that of the CdS region, confirming that selenium has been successfully doped into the CdS lattice rather than forming an independent phase. The extremely low selenium content in the CdS / MoS2 nanosheet region indicates that selenium has not been significantly doped into the MoS2 structure, consistent with the absence of characteristic MoSe2 absorption peaks in the XRD pattern. EDS spot scanning revealed that the selenium doping level is close to the theoretical value, verifying the controllability of the synthesis process. The selenium doping-induced refinement of the CdS nanostructure and the exposure of the MoS2 edges increase the specific surface area and active site density, thereby improving the photocatalytic reaction efficiency. Furthermore, the compact core-shell structure helps shorten the carrier migration path and reduce its recombination probability.

[0070] Figure 8 X-ray photoelectron spectroscopy (XPS) is used to characterize the surface chemical composition and elemental chemical states of selenium-doped CdS / MoS2 heterojunctions, confirming the elemental composition, verifying the coexistence and proportion of cadmium, molybdenum, sulfur, and selenium, and determining the oxidation state and chemical bonding state of each element. In the process of creating the image, the selenium-doped CdS / MoS2 heterojunction sample is first ground into a uniform powder and fixed onto a conductive tape, or a flat surface is formed by pressing. It is then transferred to an ultra-high vacuum sample chamber to eliminate surface contamination interference. Next, monochromatic Al Kα rays are used as the excitation source, and a full-spectrum scan is performed in constant analyzer energy mode to determine the elemental composition of the sample surface. Then, a high-resolution narrow scan is performed on the target elements, and charge correction is performed using the C 1s contamination carbon peak. Finally, software is used to fit the peaks, and the bonding environment of the doped elements and the heterojunction interface interactions are analyzed using a reference database.

[0071] From the overall spectrum in the upper left, the O 1s peak likely originates from adsorbed hydroxyl groups (~531 eV) or organic contaminants (such as adsorbed H₂O or CO₂). In the upper right spectrum, the C 1s peak is typically used for binding energy calibration (based on 284.8 eV). In the middle left spectrum, the main peak in the Se 3d band is (55.05 eV), close to the Se 1s peak. 2- The binding energy (such as Se in CdSe or MoSe2) 2- This indicates that selenium has been successfully doped into the CdS lattice or has formed the MoSe2 phase. In the right-middle plot, the S 2p orbital shows a double peak, with the peak located at approximately 161.78 eV (S). 2- (Corresponding to sulfur in CdS or MoS2), the peak splitting or the presence of shoulder peaks (around 163 eV, 167 eV) may be due to changes in the chemical environment caused by selenium doping. In the lower left figure, Mo 3d typically exhibits a double peak, with the peak located at 228.85 eV (Mo... 4+ (corresponding to MoS2) and 232.48 eV (Mo 6+(Possibly originating from surface oxidation). In the lower right image, the Cd peaks ScanA (405.91 eV) and ScanB (411.61 eV) correspond to Cd 3d... 5 / 2 and Cd 3d 3 / 2 The orbital has a spin-orbit splitting energy of 5.7 eV (411.61-405.91), which is slightly lower than the standard value for undoped CdS (~6.7 eV).

[0072] Figure 9 These are solid-state UV-Vis diffuse reflectance spectra (UV-Vis DRS spectra) of three selenium-doped CdS / MoS2 heterojunctions prepared in this invention (0.05 g, 0.10 g, and 0.15 g). These spectra characterize the optical absorption properties of the selenium-doped CdS / MoS2 heterojunction as a photocatalyst, and are used to determine its photoresponse range, band gap energy, and band structure. During testing, selenium-doped CdS / MoS2 samples with different doping amounts were taken out at a 1:100 mass ratio with dry BaSO4 powder. The BaSO4 powder was first flattened on a thin sheet, and then the selenium-doped CdS / MoS2 sample was placed in the center and flattened. The sample was then placed inside an integrating sphere, ensuring perpendicular incident light, and the UV-Vis diffuse reflectance spectra were acquired (with baseline correction performed using pure BaSO4 as a reference).

[0073] The indirect bandgap energy is then calculated using the following Kubelka-Munk function: Figure 10 :

[0074]

[0075] Where A is absorbance, hv is photon energy, n is 2, K is a constant, and E is... g This is the band gap energy.

[0076] As shown in the figure, with the increase of selenium doping concentration (0.05-0.15 g), the absorption edge of CdS shifts to the near-infrared region, and the corresponding band gap energy narrows from 3.33 eV to 3.10 eV. This is attributed to the increase of selenium doping concentration. 2- Replace S 2- The resulting lattice expansion and conduction band downshift (i.e., negative shift) further enhance the absorption edge of the selenium-doped CdS / MoS2 heterojunction upon recombination with MoS2, forming a type II band structure. This promotes the efficient transfer of photogenerated electrons from CdS to MoS2, thus broadening the maximum absorption edge of the absorption spectrum and creating a wide absorption spectrum covering the ultraviolet, visible, and near-infrared regions. Consequently, selenium doping significantly modulates the optical properties of the CdS / MoS2 heterojunction. Its broad spectral response and band synergy jointly enhance carrier separation efficiency, providing a key driving force for the hole-dominated oxidation process in photoelectrochemical water splitting for hydrogen production and methylene blue degradation.

[0077] This invention reveals the regulation of band structure and interfacial electron transfer paths in selenium-doped CdS / MoS2 heterojunctions by selenium doping, elucidates the mechanism for improving the separation efficiency of photogenerated carriers, and provides a theoretical model for multi-component synergistic modification strategies. Simultaneously, in-situ characterization techniques (such as XPS mapping) can analyze the enhancing effect of Se-S bonds on the photostability of CdS, filling the gap in the mechanism of selenium doping in suppressing photocorrosion.

[0078] The present invention also relates to an application of the above-mentioned selenium-doped CdS / MoS2 heterojunction, which is used for visible light-driven photocatalytic degradation of organic pollutants, photoelectrochemical water splitting for hydrogen production, solar cell interface layer, or photoelectrochemical sensor.

[0079] The following uses methylene blue, an industrial dye wastewater, as an example to illustrate its photocatalytic performance:

[0080] Example 4

[0081] 0.02 g of a 0.05 g selenium-doped CdS / MoS2 heterojunction was added to 50 mL of methylene blue solution (concentration 10 mg / L) to carry out photocatalytic degradation of methylene blue for 2 hours. Specifically, after adsorption in the dark for 1 hour, the sample was placed in a photocatalytic apparatus for 2 hours to complete the photocatalytic degradation.

[0082] Example 5

[0083] 0.02 g of a 0.10 g selenium-doped CdS / MoS2 heterojunction was added to 50 mL of methylene blue solution (concentration 10 mg / L) to carry out photocatalytic degradation of methylene blue for 2 hours. Specifically, after adsorption in the dark for 1 hour, the sample was placed in a photocatalytic apparatus for 2 hours to complete the photocatalytic degradation.

[0084] Example 6

[0085] 0.02 g of a 0.15 g selenium-doped CdS / MoS2 heterojunction was added to 50 mL of methylene blue solution (concentration 10 mg / L) to carry out photocatalytic degradation of methylene blue for 2 hours. Specifically, after adsorption in the dark for 1 hour, the sample was placed in a photocatalytic apparatus for 2 hours to complete the photocatalytic degradation.

[0086] In the three embodiments above, 5 mL of solution was taken every 30 minutes, centrifuged and filtered, and its absorbance was measured using a UV / Vis spectrophotometer (details below). The concentration of the degraded methylene blue industrial dye wastewater was then calculated.

[0087] The adsorption amount is calculated using the following formula:

[0088]

[0089] The degradation rate is then calculated using the following formula:

[0090]

[0091] Where A0 is the maximum absorbance of the initial solution, A t The maximum absorbance values ​​are given under different illumination times, where C0 is the initial solution concentration, and C... t Let t be the concentration of the solution at time t.

[0092] Table 1. Degradation rate of selenium-doped CdS / MoS2 heterojunctions with different selenium doping concentrations

[0093] Time 30 min 60 min 90 min 120 min Se - 0.05 g 33.48% 43.60% 58.63% 78.35% Se - 0.10 g 36.37% 57.92% 70.02% 80.20% Se - 0.15 g 36.71% 50.41% 69.64% 78.46%

[0094] From Table 1 and Figure 11 It can be seen that the 0.10g selenium-doped CdS / MoS2 heterojunction balances light absorption, dispersibility, and active sites, resulting in the highest degradation efficiency. The degradation rate after 2 hours of photocatalytic degradation is 80.20%, showing the best degradation effect. The degradation effects of other selenium-doped CdS / MoS2 heterojunctions are slightly worse. For the 0.05g selenium-doped CdS / MoS2 heterojunction, the degradation rate after 2 hours of photocatalytic degradation is 78.35%, which may be due to insufficient active sites leading to incomplete degradation. For the 0.15g selenium-doped CdS / MoS2 heterojunction, the degradation rate after 2 hours of photocatalytic degradation is 78.46%, which may be due to excessive selenium causing light scattering or agglomeration, resulting in a decrease in degradation efficiency.

[0095] This invention further illustrates the types of active groups that play a major role in the photocatalytic degradation of methylene blue (MB) by capturing free radicals.

[0096] This invention uses a 0.10g selenium-doped CdS / MoS2 heterojunction to conduct catalytic mechanism experiments. In this invention, 0.02g of a 0.10g selenium-doped CdS / MoS2 heterojunction was added to four 50mL portions of methylene blue solution (concentration 10mg / L), followed by 10mL of isopropanol solution (IPA), 0.01g of p-benzoquinone (BQ), 0.03g of disodium ethylenediaminetetraacetate (EDTA-2Na), and 0.016g of silver nitrate (AgNO3), respectively, to act as hydroxyl radicals (·OH) and superoxide radicals (·O2), respectively. - ), hole (h + ) and electrons (e - The trapping agent was prepared by irradiating the sample in a photocatalytic apparatus for 2 hours. 5 mL of each solution was then taken, centrifuged, filtered, and the absorbance was measured using a UV / Vis spectrophotometer. The results are shown in Table 2 below. Figure 12 .

[0097] Table 2. Degradation rate of methylene blue solution containing 0.10 g selenium-doped CdS / MoS2 heterojunction with different scavenging agents.

[0098] Captor Degradation rate Without captor 80.20% Isopropyl alcohol 61.75% p-Benzoquinone 54.47% Silver nitrate 40.50% Ethylene diamine-tetraacetic acid disodium salt 23.85%

[0099] From Table 2 and Figure 12 It can be seen that adding EDTA-2Na captures holes (h + After [the process], the degradation rate of methylene blue solution containing 0.10 g of selenium-doped CdS / MoS2 heterojunction was only 23.85%, and the addition of silver nitrate to capture electrons (e) [further details needed]. - After [further details needed], the degradation rate of the methylene blue solution containing 0.10 g of selenium-doped CdS / MoS2 heterojunction was 40.50%. When IPA and BQ were added to the methylene blue solution containing 0.10 g of selenium-doped CdS / MoS2 heterojunction, the degradation rate also decreased, indicating that hydroxyl radicals (·OH) and superoxide radicals (·O2) [further details needed]. - Part of it participated in the degradation reaction and played a certain role in promoting the degradation of methylene blue solution, but the effect was small, indicating that the reduction pathway was not dominant.

[0100] Therefore, EDTA-2Na significantly inhibits degradation activity, indicating that holes (h + ) is the main oxide species, directly participating in the oxidation of methylene blue or generating other reactive intermediates through indirect reactions; a small amount is electrons (e). - ), electron (e - Once captured, the reduction reaction is partially suppressed. Low selenium doping levels result in insufficient lattice distortion and limited bandgap modulation. With appropriate selenium doping levels (e.g., 0.10 g), moderate lattice expansion matches the bandgap, and holes (h0) are effectively controlled. + The dominant role is most obvious.

[0101] The selenium-doped CdS / MoS2 heterojunction prepared in this invention significantly improves the photogenerated carrier separation efficiency and visible light photocatalytic activity by controlling the selenium doping ratio and optimizing the MoS2 growth process. This provides a controllable and scalable high-efficiency photocatalytic composite material, offering a new solution to energy and environmental problems. In addition to the degradation of organic pollutants (such as methylene blue), the selenium-doped CdS / MoS2 heterojunction composite material prepared in this invention can also be used for hydrogen production via photoelectrochemical water splitting, with a hydrogen production rate several times higher than that of traditional materials. It can also be used as an interface layer in solar cells and in photoelectrochemical sensors (such as for detecting heavy metal ions). Its applications can cover clean energy production (hydrogen production via photoelectrochemical water splitting), carbon cycling (CO2 reduction), and environmental remediation (degradation of organic pollutants), promoting energy structure transformation and reducing pollution control costs.

[0102] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing selenium-doped CdS / MoS2 heterojunction, characterized in that, The method comprises the following steps: S1: ultrasonic dispersion dissolving 0.20 g of cadmium dichloride and 0.38 g of thiourea in 50 mL of deionized water to obtain a first mixed solution; S2: adding selenium powder to the first mixed solution and stirring uniformly, and then performing hydrothermal reaction at 180℃ for 12 hours to obtain a second mixed solution; S3: centrifugal washing the second mixed solution with deionized water and anhydrous ethanol alternately, and drying to obtain selenium-doped CdS nanoparticles; S4: ultrasonic dispersion dissolving 0.26 g of ammonium molybdate tetrahydrate, 0.38 g of thiourea and 0.26 g of selenium-doped CdS nanoparticles in 50 mL of deionized water to obtain a third mixed solution; S5: allowing the third mixed solution to perform hydrothermal reaction at 200℃ for 12 hours to obtain a fourth mixed solution; S6: centrifugal washing the fourth mixed solution with deionized water and anhydrous ethanol alternately, and drying to obtain a selenium-doped CdS / MoS2 heterojunction.

2. The method for preparing a selenium-doped CdS / MoS2 heterojunction according to claim 1, characterized in that, In step S2, the doping amount of selenium powder is 0.05-0.15 g.

3. The method for preparing a selenium-doped CdS / MoS2 heterojunction according to claim 1, characterized in that, In step S2 or S5, the hydrothermal reaction is performed in a blast drying oven, and the mixed solution is taken out when it is naturally cooled to room temperature.

4. The method of claim 1, wherein the selenium-doped CdS / MoS2 heterojunction is prepared by the steps of: In step S3 or S6, the centrifugal washing is performed with deionized water and anhydrous ethanol alternately for more than 3 times.

5. The method of claim 1, wherein the selenium-doped CdS / MoS2 heterojunction is prepared by the steps of: In step S3, the selenium-doped CdS nanoparticles are obtained by drying at 60℃ for 6 hours in a blast drying oven.

6. The method of claim 1, wherein the selenium-doped CdS / MoS2 heterojunction is prepared by the following steps: In step S6, the selenium-doped CdS / MoS2 heterojunction is obtained by drying at 70℃ for 2 hours in a blast drying oven.

7. The method for preparing a selenium-doped CdS / MoS2 heterojunction according to claim 1, characterized in that, The prepared selenium-doped CdS / MoS2 heterojunction has a spiral pattern.

8. Use of selenium doped CdS / MoS2 heterojunction characterized in that, The selenium-doped CdS / MoS2 heterojunction prepared by the method of any one of claims 1-7 is used for visible light-driven photocatalytic degradation of organic pollutants, photoelectrochemical water splitting to produce hydrogen, solar cell interface layer or photoelectrochemical sensor.